Investigating Culinary Vocational Students’ Sustainability Action through Learning of Physical and Chemical Changes - Sari, Ilma Indana; Agustini, Rudiana; Setiawan, Beni; Satriawan, Muhammad (FKIP Universitas Lampung, 2025)
Vocational education is pivotal in advancing the Sustainable Development Goals (SDGs), particularly SDG 12, which emphasizes responsible consumption and production. However, preliminary studies indicate that sustainability action competence among culinary vocational high school students remains relatively low. This study aims to investigate the current level of such competence and analyze how learning about physical and chemical changes within culinary contexts contributes to its enhancement. An exploratory sequential mixed-methods design utilized a validated questionnaire as the primary instrument. Findings reveal that while students generally performed well in the cognitive domain (68%), their competence in the socio-emotional domain (40%) and behavioral domain (30%) were low. Integrating the concept of substance changes with sustainable culinary practices offers promising potential for fostering sustainability competence. The implications of this study underscore the urgent need for curriculum development and instructional strategies aligned with Education for Sustainable Development (ESD), particularly within vocational culinary education.